The postnatal development of nociceptive and opioid receptor signalling pathways - Cooper, Andrew H. (2017)
The physiology and function of nociceptive and opioid signalling pathways undergo substantial postnatal maturation, and supraspinal µ-opioid receptor (MOR)-mediated control of nociceptive signalling is significantly different in juveniles and adults. Here the, mechanisms responsible for these changes were investigated. [35S]GTPγS assays utilising the MOR-selective agonist DAMGO demonstrated concentration-dependent G protein activation within rostral ventromedial medulla (RVM) tissue which was significantly different between rats aged postnatal day (P) 21 and adults (>P40) (adult: EC50 = 351.1 nM; Emax = 179% basal response; P21: EC50 = 129.3 nM; Emax = 150.9% basal response; Extra sum-of-squares F-test comparing concentration-response curves; P < 0.001). However in adult tissue, co-application of DAMGO with the ganglioside GM1 (1 µM), which has previously been shown to alter MOR G protein coupling from Gi to Gs, revealed that modulation of MOR by GM1 was not responsible for this difference (P > 0.05). Aside from expression on neurones, MOR are expressed by microglia, though the extent and functional consequences are subject to some controversy. Intracellular imaging of changes in calcium concentration using the fluorescent indicator dye Fura-2 showed that ATP-induced concentration-dependent increases in intracellular calcium were significantly increased in primary microglial cultures isolated from adult (EC50 = 2.91 µM; Emax = 0.37 Fmax - F0, the increase in 340/380 nm fluorescence ratio from baseline) versus neonatal (P1) (EC50 = 3.03 µM; Emax = 0.20 Fmax - F0; Extra sum-of-squares F-test comparing concentration-response curves; P < 0.01) brain tissue, and that co-application of DAMGO (1 µM) potentiated responses in adult microglia (EC50 = 1.56 µM; Emax = 0.57 Fmax - F0) but inhibited responses in neonatal microglia (EC50 = 2.65 µM; Emax = 0.14 Fmax - F0), suggesting postnatal alterations in microglial modulation of nociceptive signalling. Additionally, the expression of opioid receptors and their endogenous ligands human mid-brain were investigated using TaqMan RT-PCR. This did not reveal any age-related alterations in mRNA transcript levels of these genes (P > 0.05 for all), confirming previous findings in rats. Previously it has been demonstrated that painful experience during the neonatal period can have a lasting influence on pain processing and adult sensory thresholds. Investigations into opioidergic signalling as one of the mechanisms responsible were conducted with hindpaw injection of complete Freund’s adjuvant (CFA; 10 µl), which induced oedema and erythema in rats aged P1, P10 and P21. As expected this failed to induce decreases in mechanical paw withdrawal threshold (PWT) in P1 rats, in contrast to all other ages. Examining infiltrating macrophages during the acute inflammatory process revealed significant alterations between adults and neonates in cells expressing ED1 and mannose receptor, suggesting altered peripheral inflammatory processes in the neonate. Despite the aforementioned postnatal alterations in MOR-mediated control of nociception, administration of the opioid receptor antagonist naltrexone (3 mg/kg) unmasked resolved inflammatory hyperalgesia in rats injured as early as P10, showing that constitutive MOR activity is able to suppress latent pain sensitisation from an early age but not from birth, highlighting the functional immaturity of this system in early postnatal life. The impact of neonatal inflammation on hyperalgesic priming, a model of the transition from acute to chronic pain, was also investigated. CFA at P1 failed to alter adult responses to hindpaw injection of carrageenan (5 µl; 1%)-induced inflammation, did not alter the development of hyperalgesic priming (increased duration of response to hindpaw injection of PGE2; 1 µg/5 µl) and did not itself induce priming. These results suggest that previously observed life-long effects of neonatal injury are dependent on nociceptive signalling to the spinal cord rather than the presence of inflammation itself.